Gene fusions in gastrointestinal tract cancers. Issue 5 (16th March 2022) - Rahi, Hamed; Olave, Maria C.; Fritchie, Karen J.; Greipp, Patricia T.; Halling, Kevin C.; Kipp, Benjamin R.; Graham, Rondell P.
Abstract: Fusion genes have been identified in a wide array of human neoplasms including hematologic and solid tumors, including gastrointestinal tract neoplasia. A fusion gene is the product of parts of two genes that are joined together following a deletion, translocation, or chromosomal inversion. Together with single nucleotide variants, insertions, deletions, and amplification, fusion genes represent one of the key genomic mechanisms for tumor development. Detecting fusions in the clinic is accomplished by a variety of techniques including break‐apart fluorescence in situ hybridization, reverse transcription‐polymerase chain reaction, and next‐generation sequencing. Some recurrent gene fusions have been successfully targeted by small molecule or monoclonal antibody therapies (ie targeted therapies), while others are used as biomarkers for diagnostic and prognostic purposes. The purpose of this review article is to discuss the clinical utility of detection of gene fusions in carcinomas and neoplasms arising primarily in the digestive system.